A Field Study on Simulation of CO2 Injection and ECBM Production and Prediction of CO2 Storage Capacity in Unmineable Coal Seam. (27th December 2012) - He, Qin; Mohaghegh, Shahab D.; Gholami, Vida
Abstract : CO2 sequestration into a coal seam project was studied and a numerical model was developed in this paper to simulate the primary and secondary coal bed methane production (CBM/ECBM) and carbon dioxide (CO2 ) injection. The key geological and reservoir parameters, which are germane to driving enhanced coal bed methane (ECBM) and CO2 sequestration processes, including cleat permeability, cleat porosity, CH4 adsorption time, CO2 adsorption time, CH4 Langmuir isotherm, CO2 Langmuir isotherm, and Palmer and Mansoori parameters, have been analyzed within a reasonable range. The model simulation results showed good matches for both CBM/ECBM production and CO2 injection compared with the field data. The history-matched model was used to estimate the total CO2 sequestration capacity in the field. The model forecast showed that the total CO2 injection capacity in the coal seam could be 22, 817 tons, which is in agreement with the initial estimations based on the Langmuir isotherm experiment. Total CO2 injected in the first three years was 2, 600 tons, which according to the model has increased methane recovery (due to ECBM) by 6, 700 scf/d.